Too Slow a Change? Deep Habits, Consumption Shifts and Transitory Tax Policy - Inge van den Bijgaart (Center for Economic Studies and ifo Institute (CESifo), 2018)
Habits are an important cause of sluggish consumption adjustment in response to price shocks. This paper studies shifts within the consumption bundle under endogenous habit formation. I put forward a model with good-specific, or 'deep', habits that cause persistence in good-specific consumption. In addition, at the aggregate level, habits act as a benchmark against which consumption is evaluated. I evaluate dynamic consumption choices under the realistic assumption that the consumer imperfectly internalizes the habit formation process. I compare consumption choices to the welfare-maximizing choices, and determine the path of taxes or subsidies that implements first-best consumption, both when goods are produced competitively and when they are produced by monopolists. I establish that a transition to a new consumption bundle is more likely inefficiently sluggish if the persistence effect is relatively strong. Strategic pricing behavior by monopolists leads to inefficiently rapid transitions. To explore the quantitative implications of the model I consider the introduction of a 10 percent charge on a subset of goods. I find that consumption adjusts inefficiently fast; implementing first-best adjustment requires a transitory discount of up to 60 percent of the cost increase.
Keywords: D11; D62; H21; H23; 330; habit formation; projecton bias; consumption shifts; optimal taxation